Contact interaction of rough elasic solids in the presence of two highly different scales of roughness extent - Mokhel, Alexandr Nikolaevich; Salganik, Rafail Lvovich; Fedotov Аlexandr Alexandrovich (Computational Continuum Mechanics, 2008)
Using the method of successive approximations (iterations), the problem of contact interactions of squeezed semi-infinite elastic solids with rough surfaces characterized by two highly different scales of roughness extent, Λ and λ